PENGARUH DOSIS CAMPURAN PUPUK KANDANG DAN KONSENTRASI POC BMW TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TERONG PONDOH (Solanum melongena L.) VARIETAS BUTHO - Abd Mujib Al Ahmad; Pamuji Setyo Utomo; Aulia Dewi Rosanti (Universitas Islam Kadiri, 2017)
Eggplant are potential to expand as contributor the diversity nutrition of vegetable ingredients for human. Eggplant“PondohButho” is one of the superior varieties suitable for planting in the lowlands to medium lands. This study purposes to determine the effect and interaction mixture dose of manure and POC BMW to the growth and production of eggplant varieties “PondohButho”. The study was conducted on UD. RejoTani, Ds. Kemlokolegi, Kec. Baron, Kab.Nganjuk on February 10 to June 22, 2017. The results of this study; 1) there is no of interaction between mixture fertilizer and POC BMW to the growth and production of eggplantsvarieties “PondohButho” (Solanummelongena L.); 2) mixture fertilizer giving effect to observation parameter of fruit, fruit weight and fruit diameter; 3) the giving of BMW POC has a very real effect on the generative phase of the plant that is the number of fruit, fruit weight and fruit diameter on the first harvest until the fifth.